2004
DOI: 10.4319/lo.2004.49.4_part_2.1355
|View full text |Cite
|
Sign up to set email alerts
|

Haunted by the past: Evidence for dormant stage banks of microparasites and epibionts of Daphnia

Abstract: Microparasites and epibionts have important implications for the ecology and evolution of their zooplankton host populations. Many parasites and epibionts produce resistant spores that infect new hosts upon intake. We explored the hypothesis that these spores build up dormant stage banks that remain infective for several years (decades). In laboratory experiments, we exposed Daphnia magna to sediments taken from different depths in sediment cores from four different shallow water bodies. All samples analyzed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 55 publications
2
70
0
Order By: Relevance
“…An earlier study has further shown that O. bayeri spores survive drought (Vizoso et al 2005). Long-lasting parasite spore banks have been found for other Daphnia microparasites and are likely to be important for disease dynamics (Ebert 1995;Ebert et al 1997;Decastaecker et al 2002Decastaecker et al , 2004.…”
Section: Discussion (A) Diapause Drives Prevalence Cyclesmentioning
confidence: 99%
“…An earlier study has further shown that O. bayeri spores survive drought (Vizoso et al 2005). Long-lasting parasite spore banks have been found for other Daphnia microparasites and are likely to be important for disease dynamics (Ebert 1995;Ebert et al 1997;Decastaecker et al 2002Decastaecker et al , 2004.…”
Section: Discussion (A) Diapause Drives Prevalence Cyclesmentioning
confidence: 99%
“…We ignore the death rate of the parasite during exposure, since P. ramosa spores can survive several decades (Decaestecker et al 2004).…”
Section: (B) Experimental Setupmentioning
confidence: 99%
“…Despite their widespread occurrence (de Meeus and Renaud 2002) and importance in regulating predation and competition (Hatcher et al 2006), there are very few long-term or landscape-level studies on parasite population dynamics. Perhaps the best-known factors affecting parasite persistence are abiotic conditions (Morgan et al 2004, Tseng 2006, which can have powerful consequences for parasites with a vulnerable, free-living stage outside the host, even extirpating local populations (Decaestecker et al 2004, Cattadori et al 2005, Pascual and Dobson 2005. A second set of potentially powerful factors involve biotic interactions, such as competition among parasites Hudson 1986, Hatcher et al 2006).…”
Section: Introductionmentioning
confidence: 99%